Association of Serum CXCL13 with Intrarenal Ectopic Lymphoid Tissue Formation in Lupus Nephritis - De Ning He; Wen Li Chen; Kang Xia Long; Xiao Zhang; Guang Fu Dong (Journal of Immunology Research)
Aims. To assess the concentrations of serum CXCL13 and intrarenal ectopic lymphoid tissue (ELT) profiles and their correlation in the patients with lupus nephritis (LN). Methods. Serum CXCL13 levels were measured using enzyme-linked immunosorbent assays (ELISA). The expression of CD3, CD20, and CD21 in renal biopsy specimens was tested using immunohistochemical methods. Results. Serum CXCL13 levels were significantly higher in the LN group than those in the SLE group without LN and also in the type III and IV LN patients than in type V LN patients. LN patients with positive CD20 expression (CD20+ LN) had a longer disease course and poorer response to combination therapy and higher serum CXCL13 levels than CD20− LN patients. Moreover, the serum CXCL13 level was positively correlated with the number of B cells/HP in the renal tissue of LN patients. The coexpression patterns of CD3, CD20, and CD21 in the renal tissue of LN patients with different WHO pathological types were significantly different. Serum CXCL13 levels were significantly higher in ELT-2 type LN patients than in 0 or 1 type LN patients. Conclusions. This study suggested that increased serum levels of CXCL13 might be involved in renal ELT formation and renal impairment process in LN.